Evaluation of saliva and nasopharyngeal swab sampling for genomic detection of SARS-CoV-2 in children accessing a pediatric emergency department during the second pandemic wave - Diani, Erica; Silvagni, Davide; Lotti, Virginia; Lagni, Anna; Baggio, Laura; Medaina, Nicoletta; Biban, Paolo; Gibellini, Davide (Frontiers in Microbiology, 2023)
SARS-CoV-2 infection is mainly detected by multiplex real-time RT-PCR from upper respiratory specimens that is considered the gold-standard technique for SARS-CoV-2 infection diagnosis. The nasopharyngeal (NP) swab represents the clinical sample of choice, but NP swabbing can be discomfortable to the patients, especially for pediatric age subjects, requires trained healthcare personnel and may generate aerosol, increasing the intrinsic exposure risk of healthcare workers. The objective of this study was to compare paired NP and saliva samples (SS) collected in pediatric patients to evaluate whether the saliva collection procedure may be considered a valuable alternative to the classical NP swab (NPS) sampling in children. In this study, we describe SARS-CoV-2 multiplex real-time RT-PCR protocol on SS, comparing the results with the paired NP swab specimens from 256 pediatric patients (mean age of 4.24 ± 4.40) admitted to hospital emergency room AOUI Verona and randomly enrolled between September 2020 and December 2020. The saliva sampling demonstrated consistent results when compared to the NPS use. SARS-CoV-2 genome was detected in 16 out of 256 (6.25%) NP samples whose 13 (5.07%) were positive even when paired saliva samples were analyzed. Moreover, SARS-CoV-2 negative NPS and SS were consistent and the overall concordances between NPS and SS were detected in 253 out of 256 samples (98.83%). Our results suggest that saliva samples may be considered a valuable alternative to NPS for the SARS-CoV-2 direct diagnosis with multiplex real-time RT-PCR in pediatric patients.